USING LINEAR REGRESSION TO ANALYZE ECONOMICS CONTENT MASTERY AND LEARNER’S AUTONOMY TOWARDS ENGLISH WRITING COMPETENCE - Paskalina Widiastuti Ratnaningsih (JAMBI-ENGLISH LANGUAGE TEACHING, 2019)
English is used widely in education area. It is also used in higher education. Many universities put English in the curriculum. In industrial revolution 4.0., English has an important role. English for Economics is needed to prepare students to master business English and English as an international language. Writing is as the focus of English skill in this study. To support good English writing, Economics content mastery is needed before learning English. Learner’s autonomy in the process of writing is also needed for writing development. In this study, economics content mastery and learner’s autonomy were identified to perceive the effect on the competence in English writing. The method used was multiple linear regressions as there were two independent variables in this study. Closed-ended questionnaire was used as the instrument. The result from linear regression showed that there were partial effects and simultaneous effect of economics content mastery and learner’s autonomy towards English writing competence. It means that H1, H2, and H3 were accepted and Ho was rejected in which there were significant effects among the variables. It can be interpreted that economics content while studying English for Economics and learner’s autonomy in terms of independently learning English writing were significantly needed in order to enhance English writing competence. The practical implication from this study is the students do not only need to learn English, but also learn Economics content and develop independent learning for autonomy learning in the process of English for Economics learning activities. Keywords: Writing Competence, English, Economics Content, Learner’s Autonomy